Trust issues in a service oriented environment - Hussain, Farookh Khadeer; Chang, Elizabeth; Dillon, Tharam S. (IEEE Computer Society, 2006)
Service Oriented Environment (SOE) is a new paradigm for carrying out business activities on the internet. In this paper, I give an introduction to the concept of service oriented environment and discuss the different activities carried out in the SOE and different entities involved in SOE. The issues related to trust in service oriented environment are proposed and explained.